Вплив віртуальної свободи на становлення особистості - Іванова, Христина; Ivanova, Khrystyna (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто вплив віртуальної свободи на становлення особистості, проаналізовано основні ідеї вчених, які досліджували цю проблему. Зазначено, що віртуальна свобода – це один із феноменів людської діяльності, який безпосередньо впливає на формування світогляду та становлення ціннісних орієнтацій. Для свободи, яка існує у віртуальному просторі, властивий амбівалентний характер і те, що вона може мати як позитивні (самореалізація, комунікація, підвищення освітнього рівня тощо), так і негативні наслідки (кліпове мислення, «розщеплення» свідомості, деперсоналізація та ін.) для особистостя людини. Питання про вплив віртуальної свободи залишається актуальним, адже відбувається постійна віртуалізація всіх сфер особистісного життя індивіда. The article deals with the role of virtual freedom in people's lives. Virtual freedom is a new world’s phenomenon. It shows the influence of virtual freedom on the personality's formation, their world view and values. Virtual freedom affects the values formations such the value of freedom, friendship, morality, self-realization, creativity, etc. Virtuality allows a person to be free from the power of traditions and forms a new vision of freedom and responsibility. Besides it can form the immoral traits. It’s cruelty, coercion, excess hedonism and others. The value of information and knowledge is divided. Gradually there is a transition from altruistic values to selfish. Virtual freedom is of an ambivalent nature and can have positive and negative implications. The possibility of self-realization, communication and creativity are the main positive effects. The main negative manifestations of religious freedom are depersonalization, the formation of clip art and the splitting of consciousness. Such freedom gives the person the opportunity to compensate for the lack of communication. There is a new type of communication, which is devoid of direct emotions and feelings. Today, freedom of the individual is largely determined by access to Internet resources. This issue still remains relevant, as far as an active virtualization of all spheres of life is happening all around.
The Influence of Virtual Freedom on the Personality's Formation
Keywords: феномен; віртуальність; свобода; світогляд; вибір; самореалізація; phenomenon; virtuality; freedom; worldview; choice; self-realization